Birth of mice from meiotically arrested spermatocytes following biparental meiosis in halved oocytes. (19th May 2022) - Ogonuki, Narumi; Kyogoku, Hirohisa; Hino, Toshiaki; Osawa, Yuki; Fujiwara, Yasuhiro; Inoue, Kimiko; Kunieda, Tetsuo; Mizuno, Seiya; Tateno, Hiroyuki; Sugiyama, Fumihiro; Kitajima, Tomoya S; Ogura, Atsuo
Abstract: Microinjection of spermatozoa or spermatids into oocytes is a major choice for infertility treatment. However, the use of premeiotic spermatocytes has never been considered because of its technical problems. Here, we show that the efficiency of spermatocyte injection in mice can be improved greatly by reducing the size of the recipient oocytes. Live imaging showed that the underlying mechanism involves reduced premature separation of the spermatocyte's meiotic chromosomes, which produced much greater (19% vs. 1%) birth rates in smaller oocytes. Application of this technique to spermatocyte arrest caused by STX2 deficiency, an azoospermia factor also found in humans, resulted in the production of live offspring. Thus, the microinjection of primary spermatocytes into oocytes may be a potential treatment for overcoming a form of nonobstructive azoospermia caused by meiotic failure. Synopsis: Mouse primary spermatocytes can complete meiosis following injection into meiotic oocytes, but with severe chromosome segregation errors. Reduction of the cytoplasm of the oocytes prevents these chromosomal errors and enables efficient production of spermatocyte‐derived offspring. Spermatocyte chromosomes within oocytes show premature separation at MI and seem to be defective in activating spindle assembly checkpoint. The predominant error pattern is predivision of sister chromatids, which can be suppressed by reduction of the ooplasm. This technology enabled the production of offspring from azoospermic male mice lacking Stx2, an azoospermic factor in humans. Abstract : Mouse primary spermatocytes can complete meiosis following injection into meiotic oocytes, but with severe chromosome segregation errors. Reduction of the cytoplasm of the oocytes prevents these chromosomal errors and enables efficient production of spermatocyte‐derived offspring.